Less than 5% Potential High Growth Enterprises Kept the National Economy Growth during the Crisis - Pšeničny, Viljem; Maček, Anita; Vidovič, Danilo (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
.
Keywords: .